BODY LANGUAGE AND VOICE DEAVELOPING : Body language exists in both animals and humans, but this article focuses on interpretations of human body language.When it comes to voice, voice (or vocalization) is the sound produced by humans and other vertebrates using the lungs and the vocal folds in the larynx, or voice box. In terms of observable body language, non-verbal (non-spoken) signals are being exchanged whether these signals are accompanied by spoken words or not. - Маханов, Жавохир (Журнал иностранных языков и лингвистики, 2023)
This article gives information about body language, which is a type of Communication. They are physical behaviors, as opposed to words, are used to express or communicate the information. Body Language is a significant aspect of modern communications and relationships. Therefore, it is very relevant to management or leadership and to all aspects of work and business where communications can be seen and physically observed among people. Such behavior includes facial expressions, body posture, gestures, eye movement, touch and the use of space. Body language, on the other hand, does not have a grammar system and must be interpreted broadly, instead of having an absolute meaning corresponding with a certain movement, so it is not a language, and is simply termed as a "language" due to popular culture.